A Proposed Classification of Intraretinal Microvascular Abnormalities in Diabetic Retinopathy Following Panretinal Photocoagulation - Shimouchi, Akito (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To investigate the characteristics of intraretinal microvascular abnormalities (IRMAs) before and after panretinal photocoagulation (PRP) for diabetic retinopathy (DR) by using optical coherence tomography angiography (OCTA). METHODS: Forty-six eyes of 29 patients with DR were included (26 eyes with severe nonproliferative diabetic retinopathy [SNPDR] and 20 eyes with proliferative diabetic retinopathy [PDR]). En face OCTA images of IRMAs in a 6 × 6-mm area were acquired by using Cirrus 5000 with AngioPlex. The morphological changes in IRMAs were evaluated before and after PRP. The changes in the IRMAs were divided into five subtypes: unchanged; tuft regression; reperfusion; mixed (combined tuft regression/reperfusion); and worsening (new appearance of tuft). RESULTS: Unchanged IRMAs were identified in 15 SNPDR eyes and 2 PDR eyes; all neovascularization (NV) had regressed after PRP. Tufts were more frequently observed in the PDR eyes (15/20, 75%) than in the SNPDR eyes (8/26, 31%) (P = 0.003), and two tufts tended to exceed the inner limiting membrane, which showed progression to NV before PRP. The reperfusion phenomenon was observed in 7/26 SNPDR eyes and 4/20 PDR eyes, including the mixed type, and showed two vascular patterns: abnormal (dilated, tortuous, and twisted) and normal vessels. The worsening type was observed in 1/26 SNPDR eye and 2/20 PDR eyes. CONCLUSIONS: OCTA enabled classification of IRMA into more detailed types. The unchanged and reperfusion types suggested that IRMAs had aspects of remodeling. However, IRMAs with tufts were observed in 75% of the PDR eyes, and the tufts had aspects of NV.